Newborn with Refractory Seizures due to Hemimegalencephaly and Tuberous Sclerosis Complex: Case Report and Literature Review - Rondagh, Mathies; de Vries, Linda S.; Meeren, Lotte E. van der; Tromp, Selma C.; Peeters-Scholte, Cacha M.P.C.D.; Toirkens, Menno J.P.; Steggerda, Sylke J. (Neuropediatrics, 2025)
Hemimegalencephaly (HME) is a rare congenital disorder that is initiated during embryonic development with abnormal growth of one hemisphere. Tuberous sclerosis complex (TSC), a genetic disorder, is rarely associated with HME.We present a case of a newborn with HME with a confirmed mutation in the TSC-1 gene and describe the clinical course, findings on amplitude-integrated electroencephalography (aEEG), cranial ultrasound (CUS), MRI, and the postmortem evaluation. Furthermore, we conducted a comprehensive literature review of all reported newborns with HME and a genetically confirmed TSC mutation.This infant experienced therapy-resistant seizures after birth despite treatment with multiple antiseizure medications. CUS and MRI revealed HME of the left hemisphere. Early functional hemispherectomy, around the age of 3 months, was considered but dismissed after multidisciplinary evaluation, medical ethical consultation, and multiple discussions with the parents. Care was redirected due to worsening clinical and neurologic conditions, increasing respiratory insufficiency, and ongoing therapy-resistant seizures. Postmortem evaluation of the brain revealed hamartomatous brain changes and irregular gyration of the enlarged hemisphere. in addition, these changes were also present in the previously considered unaffected side, raising thoughts about the potential effectiveness of functional hemispherectomy.This case report illustrates that in cases with TSC abnormalities might not be confined solely to the initially considered affected side. This can have important therapeutic implications.
Keywords: hemimegalencephaly; neonatal seizures; tuberous sclerosis complex; postmortem; neuroimaging